Surface diffraction on a ψ‐circle diffractometer using the χ‐axis geometry. (15th May 2013) - Fister, Tim T.; Fuoss, Paul H.; Fong, Dillon D.; Eastman, Jeffrey A.; Folkman, Chad M.; Hruszkewycz, Stephan O.; Highland, Matthew J.; Zhou, Hua; Fenter, Paul
Abstract : The restricted volume above and below the sample on a six‐circle diffractometer can limit the size and complexity of sample environments used in surface diffraction studies. An alternative configuration of the diffractometer, where the sample normal is aligned parallel to the χ axis, allows for ample space above and below the χ circle for instrumentation. The merits of this approach are outlined and angles are derived for the diffraction condition for constant‐incident‐angle, constant‐sample‐azimuthal‐angle and specular geometries. Using a version of this code written for SPEC (http://www.certif.com/content/spec/), sample specular and nonspecular crystal truncation rods measured from a 5 nm‐thick thin film are presented.